The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1039/c2cc37891d
|View full text |Cite
|
Sign up to set email alerts
|

Highly regioselective synthesis of fused seven-membered rings through copper-catalyzed cross-coupling

Abstract: A highly efficient protocol of copper catalysis for the one-pot synthesis of fused dibenzo[b,f][1,4]oxazepines is reported. The transformation involves a Smiles rearrangement, leading to the completely different regioselectivity from the classical cross-coupling. The easy reaction of aryl chlorides as substrates enhances the practical application of the methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Based on previous reports 8,25 and on our preliminarily mechanistic experiments, a possible reaction mechanism was proposed (Scheme 4). Under basic conditions, the intermediate A is initially formed through direct nucleophilic substitution of the phenolic oxygen anion with the 4,5-dichloropyridazin-3-one.…”
Section: Letter Syn Lettmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on previous reports 8,25 and on our preliminarily mechanistic experiments, a possible reaction mechanism was proposed (Scheme 4). Under basic conditions, the intermediate A is initially formed through direct nucleophilic substitution of the phenolic oxygen anion with the 4,5-dichloropyridazin-3-one.…”
Section: Letter Syn Lettmentioning
confidence: 96%
“…[18][19][20][21] On the basis of this concept, many N-and O-containing fused heterocycles have been conveniently produced with high efficiencies. 8,[22][23][24] Inspired by the reported works, 9,10,25 we developed a one-pot, highly regioselective protocol for the construction of indole-fused pyridazino [4,5-b] [1,4]benzoxazepin-4(3H)-ones through a Smiles rearrangement, using readily available starting materials.…”
Section: Letter Syn Lettmentioning
confidence: 99%
“…Sang et al [8] reported a protocol for the one-pot synthesis of indole/benzimidazole-fused DBOs 9 via copper catalysis (Scheme 2). The reaction involves a copper initiated C-N and C-O coupling of 2-halophenols 7 and 2-(2-halophenyl)-1H-indoles 8 in one pot.…”
Section: Synthetic Strategies To Dbosmentioning
confidence: 99%
“…Ullman coupling/rearrangement/cyclization cascades are not limited to benzamides and Zhang et al. reported a related reaction with 2‐arylindole 31 to afford a pentacyclic ring system 33 as a single regioisomer (Scheme ) . A range of halogenated phenols 32 were used for the rearrangement and a single halogen is sufficient for activation (i.e., I 90 % and Br 58 %).…”
Section: Two‐electron Smiles Rearrangementmentioning
confidence: 99%